Ovarian Torsion in Pediatric Patients - Annalisa Rudser MD; Kyle Rudser PhD; Richard J. Patterson MD; Heidi VanderVelden MS; Samuel Reid MD (SAGE Publishing, 2014)
Objectives . To examine associated clinical features and evaluate published criteria regarding volumetric diagnosis of ovarian torsion (OT). Methods . Retrospective case-control study of patients presenting to an emergency department who underwent pelvic imaging for acute abdominal or pelvic pain. Cases were found to have OT at surgery. Controls received clinical diagnosis of either acute pelvic pain or ovarian cyst. Results . The sensitivity for OT using a cutoff AV of <20 mL was 50% (95% confidence interval [CI] = 35% to 65%); specificity was 29% (95% CI = 15% to 43%). The sensitivity for OT using a cutoff AV of >75 mL was 18% (95% CI = 7% to 30%); specificity was 93% (95% CI = 85% to 100%). The ratio of affected-side to unaffected-side AV of >15 had a sensitivity of 16% (95% CI = 5% to 27%); specificity was 98% (95% CI = 93% to 100%). Conclusions . The published criteria regarding the volumetric diagnosis of OT were inadequately sensitive for detecting OT. However, an affected-side AV >75 mL and an AV ratio >15 were reasonably specific.